Outcomes of different surgical procedures for optic disc pit: a meta-analysis - Hussain A. Khaqan; Raheela Naz; Hafiz A. ur Rehman; Laraib Hassan; Nabeel Akram; Hafiz M. Farooqui; Ahmad Fauzan; Asad M. Khan (Journal of the Egyptian Ophthalmological Society, 2024)
Objective To assess the surgical outcomes of pars plana vitrectomy (PPV) in conjunction with various adjuvant procedures for optic disc pit maculopathy (ODPM). Methods We conducted a literature search to identify clinical studies and case series of surgically treated OPM patients. (1) greater than two patients, (2) surgical treatment and (3) reporting of pre and postoperative visual acuity data were inclusion criteria. We excluded review articles and studies unavailable in the English language. One-way analysis of variance, Pearson’s chi-squared test and straightforward linear regression were used to analyze the results. Results A total of 838 studies were initially identified as potentially relevant studies. After removing duplicates and screening titles and abstracts, the eligibility of 86 full-text articles was evaluated. There were 50 studies included in the meta-analysis. We identified the following commonly reported techniques: juxtapapillary laser alone, PPV alone or with juxtapapillary laser (PPV/JPL), internal limiting membrane peeling (PPV/ILMP), both ILMP and JPL (PPV/ILMP/JPL), inner retinal fenestration (PPV/IRF), autologous platelet concentrate (PPV/APC), macular buckling alone or with PPV, PPV with ocriplasmin (PPV/OCR) and PPV with autologous scleral flap. All groups showed an improvement in best-corrected visual acuity compared with baseline, with no significant differences between groups. The average OPM resolution rate for all groups was 70% (range: 56–100%), and the average resolution duration was 9.1 months. Central macular thickness was diminished in the PPV, PPV/JPL, and PPV/ILMP groups, but there were no significant differences between groups. There was no effect on the outcomes. Analyses of linear regression revealed significant correlations between preoperative best-corrected visual acuity and the aforementioned outcome measures. The rate of complete anatomic success and visual improvement following PPV is ∼85%. Anatomic and visual success rates for PPV alone are 89% and 100%, respectively, according to subgroup analysis. Gas tamponade, laser and ILMP during vitrectomy are less promising, whereas PPV with ILM flap stuffing may yield better results than cases without it. Conclusion We did not find a significant difference in functional outcomes between the various surgical procedures used to treat OPM. Based on the available evidence, PPV is effective for ODPM, while gas tamponade, laser and ILMP should be used with caution. This study is limited by its reliance on retrospective studies and publication bias towards positive outcomes.